Volume, effusion rate, and lava transport during the 2021 Fagradalsfjall eruption : results from near real-time photogrammetric monitoring - Pedersen, G. B. M.; Belart, J. M. C.; Oskarsson, B. V.; Gudmundsson, M. T.; Gies, N.; Hognadottir, T.; Hjartardottir, A. R.; /Pinel, Virginie; Berthier, E.; Durig, T.; Reynolds, H. I.; Hamilton, C. W.; et al. (2022)
The basaltic effusive eruption at Mt. Fagradalsfjall lasted from 19 March to 18 September 2021, ending a 781-year repose period on Reykjanes Peninsula, Iceland. By late September 2021, 33 near real-time photogrammetric surveys were completed using satellite and airborne images, usually processed within 3-6 hr. The results provide unprecedented temporal data sets of lava volume, thickness, and effusion rate. This enabled rapid assessment of eruption evolution and hazards to populated areas, important infrastructure, and tourist centers. The lava flow field has a mean lava thickness exceeding 30 m, covers 4.8 km(2) and has a bulk volume of 150 +/- 3 x 10(6) m(3). The March-September mean bulk effusion rate is 9.5 +/- 0.2 m(3)/s, ranging between 1 and 8 m(3)/s in March-April and increasing to 9-13 m(3)/s in May-September. This is uncommon for recent Icelandic eruptions, where the highest discharge usually occurs in the opening phase.